2019
DOI: 10.1590/s2175-97902019000218285
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of citrus lemon on inflammation and adipokine levels in acrylamide-induced oxidative stress in rats

Abstract: The high exposure to acrylamide (AA) due to smoking and increased consumption of processed and fast foods in recent years, has become one of the health threatening problems. This study examined the effect of lemon juice on inflammation and adipokines in acrylamide-induced oxidative stress in rats. Forty animals were divided into five groups. Toxicity was induced by AA (35mg/kg) for two weeks in all groups except normal control group. After that, lemon juice in three doses was administrated to treatment groups … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 38 publications
2
8
0
Order By: Relevance
“…A similar study demonstrated that sesame oil supplementation reduced serum MDA levels in streptozotocin‐induced diabetic rats. [ 43 ] In addition, the content of MDA in liver of H‐CSO group was significantly decreased than HFD group ( p < 0.05, Figure 4F). Similarly, other studies have shown that the pretreatment with Silybum marianum seed oil markedly diminished the hepatic MDA concentration in CCl 4 ‐induced mice.…”
Section: Resultsmentioning
confidence: 97%
“…A similar study demonstrated that sesame oil supplementation reduced serum MDA levels in streptozotocin‐induced diabetic rats. [ 43 ] In addition, the content of MDA in liver of H‐CSO group was significantly decreased than HFD group ( p < 0.05, Figure 4F). Similarly, other studies have shown that the pretreatment with Silybum marianum seed oil markedly diminished the hepatic MDA concentration in CCl 4 ‐induced mice.…”
Section: Resultsmentioning
confidence: 97%
“…Strikingly, the discovery of ACR formation in carbohydrate‐rich foods processed at high temperature (>120°C) has raised significant human health concerns (Abd‐Elsalam et al, 2021). For example, the International Agency for Research on Cancer classifies ACR as a probable human carcinogen (Haidari et al, 2019). Glycinamide, the hepatic metabolite of ACR, binds and forms DNA adduct to cause genetic damage.…”
Section: Introductionmentioning
confidence: 99%
“…However, systematic studies have chiefly implicated oxidative stress in the molecular mechanism of ACR testicular toxicity (Al‐Karim et al, 2015; Erdemli et al, 2019; Gül et al, 2021; Kucukler et al, 2020; Radad et al, 2020; Sun et al, 2018). Acrylamide undergoes hepatic metabolism through glutathione conjugation or oxidation yielding glycinamide which promotes membrane peroxidation and generation of reactive oxygen species (ROS) (Haidari et al, 2019). Acrylamide thus induces decline in antioxidant defence milieu to provoke reproductive derangement and DNA damage in delicate organs (Hamdy et al, 2020; Radad et al, 2020; Sengul et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Recent report suggests that the level of CRP and TNF-α are significantly elevated after ACR treatment with dose of 35 mg/kg for 2 weeks. The increase could be attributed to cytokines and adipokines dysregulation due to ACR-induced oxidative stress [54]. Ameliorative effects of presupplementation with chlorella vulgaris (CV) on most studied parameters recorded in the present study.…”
Section: Groupsmentioning
confidence: 48%